Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.5 - Factoring Polynomials - Exercise Set - Page 69: 80



Work Step by Step

Regroup to obtain: $=(x^3+2x^2) + (-x-2)$ Factor out $x^2$ in the first group and $-1$ in the second to obtain: $=x^2(x+2) + (-1)(x+2) \\=x^2(x+2) - 1(x+2)$ Factor out the GCF of $x+2$ to obtain: $=(x+2)(x^2-1) \\=(x+2)(x^2-1^2)$ Factor the difference of two squares using the formula $a^2-b^2=(a-b)(a+b)$ where $a=x$ and $b=1$ to obtain: $=(x+2)(x-1)(x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.